MODERASI BERAGAMA MELALUI KURIKULUM FIQIH BERBASIS KITAB KUNING: STUDI KOLABORASI PENDIDIKAN PESANTREN DAN PERGURUAN TINGGI - Diana Puspita Kusuma Wardani; Elisa Nafilatun Naja (Yayasan An-Nur Meunara Baro, 2026)
This study aims to analyze the collaborative curriculum model between higher education and pesantren in strengthening religious moderation through fiqh learning at Universitas Kiai Abdullah Faqih (UNKAFA). The research focuses on the integration of classical Islamic texts into the university curriculum and the mechanism of internalizing moderation values. This study employs a qualitative approach with a case study design. Data were collected through in-depth interviews, classroom observations, and document analysis of curriculum and fiqh teaching materials. The findings show that UNKAFA implements an embedded curriculum model by integrating the classical text Yaqutun an-Nafis as the main reference in fiqh learning across all study programs. This text serves as an epistemological foundation shaping students’ intellectual framework. Curriculum differentiation and stratification, along with the application of a spiral curriculum, enable gradual, in-depth, and contextual learning. The internalization of religious moderation is carried out through a contextual hermeneutical approach, where classical texts are dialogically interpreted in relation to contemporary realities. This model successfully fosters students’ moderate religious attitudes, including tolerance (tasamuh), balance (tawazun), and moderation (tawassut). Students demonstrate the ability to understand Islamic law contextually and avoid rigid or extreme interpretations. In conclusion, the collaborative curriculum model at UNKAFA effectively integrates pesantren traditions with modern higher education, contributing to the development of a moderate, contextual, and intellectually grounded Islamic education.